Effects of high-intensity multi-modal exercise training (HIT-MMEX) on bone mineral density and muscle performance in postmenopausal women. A Pilot randomized controlled trial - Riaz, Huma; Babur, Muhammad Naveed; Farooq, Ahsen (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the effects of high-intensity multimodal exercise training on bone mineral density and muscle performance in postmenopausal women. Method: The two-armed, parallel, pilot randomised controlled trial was conducted from November 2020 to July 2021 at Riphah Rehabilitation Centre, Rawalpindi, Pakistan, and comprised women aged 45-70 having been in the post-menopause phase for at least 3 years, with body mass index <30, community ambulant and willing to have exercise therapy. The subjects were randomised into two equal groups. The experimental group A received supervised high-intensity resistance, weight-bearing, balance and mobility training twice weekly for 8 months. The control group B received low-to–moderate intensity exercises. Femoral neck and lumbar spine bone mineral density (g/cm2) were taken through a dual-energy X-ray absorptiometry scan. Muscle performance was measured using 1 repetition maximum for leg and trunk extensors, and 30 sec sit to stand test. Data was analysed using SPSS 21. Results: Of the 101 women screened, 28(27.7%) were enrolled; 14(50%) in group A having mean age 53.36±6.28 years, and 14(50%) in group B having mean age 51.71±4.82 years (p>0.05). Group A showed significantly more improvement than group B both with respect to lumbar spine bone mineral density and muscle performance (p<0.05). Conclusion: Supervised high-intensity multimodal exercise training protocol had a positive effect on lumbar spine bone mineral density and muscle performance in postmenopausal women. Clinical Trial Number: NCT04653350 Link https://clinicaltrials.gov/ct2/show/NCT04653350 Key Words: Osteoporosis, Post-menopausal, Bone density, Strength, Muscle.